Zoning System in Biodiversity Conservation and Marine Ecological Sustainability: An Emic Perspective of the Bajo People in Southeast Sulawesi - Ambo Upe; Andi Tenri; Shadrack Kipkoech Sitienei; Ali Hadara; Pendais Hak; Achmad Syarahil (CV. Literasi Indonesia, 2022)
The spirit of fisheries modernization or known as the blue revolution is to transform traditional fishing communities into modern fishermen. This paradigm aims to utilize marine resources in a modern way to increase the income of fishing communities in particular, and the income of the State in general. However, in its implementation, the use of maritime resources tends to lead to massive exploitation, thus causing damage to biodiversity and threatening ecological sustainability. Therefore, it is necessary to manage sustainable marine resources as carried out by the Bajo people. This study aims to describe the zoning system in marine resource conservation, the values of local wisdom contained in the marine conservation system, and its benefits in ecological sustainability. Methodologically, this study uses a qualitative approach, a type of ethnography. Data was collected through a process of in-depth interviews and observations. There are three main issues in the findings of this research. First, there are three zoning systems in the management of marine resources in the Bajo community, namely: sacred zone (Toroh Pamali), coral conservation zone (Tubba Dikatutuang), and free fishing zone (Sapa). Second, the existence of the zoning system is based on the local wisdom values of the Bajo community in Sama Bahari Village, including social, economic, and ecological values. Third, the existence of the zoning system to date is considered quite effective in maintaining the ecological, social, and economic sustainability of the Bajo community in Wakatobi Regency, Southeast province.